Changes of hydration measures in elite National Collegiate Athletic Association Division I wrestlers - Borden, E. C.; Kraemer, W. J.; Walrod, B. J.; Post, E. M.; Caldwell, L. K.; Beeler, M. K.; DuPont, W. H.; Anders, J. P.; Martini, E. R.; Volek, J. S.; Maresh, C. M. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To evaluate the changes in the state of hydration in elite National Collegiate Athletic Association (NCAA) Division I college wrestlers during and after a season. Methods: Ohio State University wrestling team members (N=6; mean [SD] age=19.6 [1.1] y; height=171.6 [2.9] cm; body mass=69.5 [8.1] kg) gave informed consent to participate in the investigation with measurements (ie, body mass, urine-specific gravity [USG; 2 methods], Visual Analog Scale thirst scale, plasma osmolality) obtained during and after the season. Results: Measurements for USG, regardless of methods, were not significantly different between visits, but plasma osmolality was significantly (P=.001) higher at the beginning of the season—295.5 (4.9) mOsm/kg compared with 279.6 (6.1) mOsm/kg after the season. No changes in thirst ratings were observed, and the 2 measures of USG were highly correlated (r>.9, P=.000) at each time point, but USG and plasma osmolality were not related. Conclusions: A paradox in the clinical interpretation of euhydration in the beginning of the season was observed with the USG, indicating that the wrestlers were properly hydrated, while the plasma osmolality showed they were not. Thus, the tracking of hydration status during the season is a concern when using only NCAA policies and procedures. The wrestlers did return to normal euhydration levels after the season on both biomarkers, which is remarkable, as previous studies have indicated that this may not happen because of the reregulation of the osmol-regulatory center in the brain.